(untitled) (International Journal of Engineering and Computer Science, 2017)
For a PV array, system monitoring is considered important to analyze the stability and performance. The simple monitoring system involves a data logging system with wired cables for transmitting data. Removing all those drawbacks observed in the existing system this proposed work is designed for the wireless monitoring of photovoltaic cell as a high precision solar array monitoring system. It is planned to measure the basic PV array characteristics like Module Temperature (T), Open Circuit Voltage (Voc), Short Circuit Current (Isc) and wirelessly transmit the data into real time GUI in the computer. The GUI was developed using the PROCESSING software. The commercially available WPAN hardware module ZigBee is used for implementation with API protocol for exchanging information. A sensor node with XBee and a set of analog sensors (eliminating the use of controllers at the sensor node) for measuring current and voltage generated in the PV array has been deployed. A coordinator node with Atmel microcontroller and Xbee connected with a PC to analyze the parameters.